Strategi Greenpeace Indonesia Dalam Advokasi Permasalahan Polusi Kabut Asap Di Sumatera Selatan - Andrian Sani; Ryllian Chandra Eka Viana; Reni Rentika Waty (CV. ITTC INDONESIA, 2025)
This study examines Greenpeace Indonesia’s strategies in advocating against the haze pollution caused by forest and land fires in South Sumatra. The research questions focus on Greenpeace’s role in haze advocacy, the approaches and strategies employed, and the challenges faced during the advocacy process. A qualitative method was applied, gathering data through interviews, observations, and document analysis. The findings reveal that Greenpeace Indonesia actively organizes advocacy activities combining scientific approaches, public campaigns, legal actions, and empowerment of local communities. Greenpeace also collaborates with local organizations to strengthen the impact of its advocacy. However, challenges such as limited public understanding, restricted access to data, and legal and political obstacles remain significant hurdles. The study recommends enhancing synergy with local communities and increasing data transparency to improve advocacy effectiveness. This research provides valuable insights into the role of environmental organizations in addressing ecological issues in Indonesia.